The book of real-world negotiations : successful strategies from business, government, and daily life - Weiss, Joshua N. (John Wiley & Sons, Inc., 2020)
"This book will be the first of its kind to solely focus on real world negotiation examples and cases. Unlocking Yes will speak to the general public about what is possible through negotiation. The average person usually brings skepticism to the table and does not know how to negotiate effectively -- giving up prematurely or reaching deals that leave value on the table. After reading Unlocking Yes and the real-world examples within the lay person will have no choice but to finally grasp the true power of negotiation. Another critical audience for Unlocking Yes are instructors and students of negotiation. Negotiation is now being taught in virtually all law schools, many business schools, and in the field of conflict resolution. Instructors and students with be provided with rich examples to analyze and learn from. By the time people will stop saying "a solution is not possible" and instead, roll up their sleeves and keep negotiating until their find their own solution. They will finally realize negotiation is indeed the art of the possible. The book will be organized around key concepts in negotiation. The cases will be bunched around these different concepts, including (but not limited to): A. Win Win outcomes, B. Understanding underlying interests and how they made agreements possible, C. Creative option generation, D. Best Alternative to Negotiated Agreements (BATNA), E. Negotiating successfully in the face of power F. Cross Cultural Negotiation Success"--